Religiosity versus rationality: depositor behavior in Islamic and conventional banks - Aysan, Ahmet F.; Disli, Mustafa; Duygun, Meryem; Ozturk, Huseyin (Elsevier, 2018)
This study investigates the behavioral aspects of Islamic bank depositors in a dual banking system. By categorizing depositors into groups based on the amount of their deposited funds, we estimate the responses of these groups to interest rate changes. We take the findings of conventional banks as a comparative baseline and investigate the extent to which the changes in different Islamic depositor groups differ from conventional depositor groups. The findings show that depositors in both Islamic and conventional banks respond to interest rate changes. The analysis indicates that Islamic bank depositors are more responsive when their deposit sizes are larger. When Islamic bank depositors' opportunity costs rise due to a rise in the interest rate, they do not hesitate to withdraw deposits. The relation between interest rate changes and deposits is more robust in Islamic banks than in conventional banks.